Preoperative planning of medial opening wedge high tibial osteotomy using 3D computer-aided design weight-bearing simulated guidance: Technique and preliminary result. (1st March 2019) - Chernchujit, Bancha; Tharakulphan, Suthee; Prasetia, Renaldi; Chantarapanich, Nattapon; Jirawison, Choen; Sitthiseripratip, Kriskrai
Background: High tibial osteotomy (HTO) is an established treatment for uni-compartmental osteoarthritis with varus deformity in relatively active young patients with good knee mobility. The most important factor for success and low complications of HTO is the precise correction of osteotomy. The objective of this study was to evaluate the accuracy of pre-operative planning of open-wedge HTO using t3D computer-aided design (CAD) weight-bearing simulated guidance technique for the succession of surgery. Materials and methods: Nineteen patients who met the inclusion criteria were recruited between July 2013 and June 2014. 3D CAD weight-bearing simulated guidance technique was obtained from standard anterior–posterior, lateral of hip-to-ankle full leg standing radiographs, and computed tomography (CT) scan provided the weight-bearing corrective axis of preoperative planning and predictive corrective mechanical axis value. Post-operative mechanical axis value was obtained after surgery. Results: This comparative study between the predictive corrective, using 3D CAD weight-bearing simulated guidance technique, and post-operative mechanical axis value, analysed with t -test statistical analysis, showed the insignificant difference ( p > 0.05). Conclusion: We conclude that the 3D CAD weight-bearing simulated guidance technique has good accuracy as preoperative planning of open-wedge HTO for succession surgery.